The non-canonical poly(A) polymerase FAM46C acts as an onco-suppressor in multiple myeloma - Seweryn Mroczek (Nature Portfolio, 2017)
FAM46C is one of the most frequently mutated genes in multiple myeloma (MM), but its molecular function remains unknown. Here the authors show that FAM46C is a poly(A) polymerase and that loss of function of FAM46C drives multiple myeloma through the destabilisation of ER response transcripts.